(untitled) (Journal of Civil Engineering Researchers, 2023)
Seismic Strengthening offers a cost-effective and sustainable solution for constructing bridges in seismic zones. In these rehabilitation interventions, Fiber Reinforced Polymer (FRP) composites are often used instead of steel members due to their lightweight nature, high strength, and excellent corrosion resistance. Researchers are now focusing on creating innovative FRP-concrete hybrid structures. This study specifically investigates the numerical modeling of the response of a hybrid FRP-concrete jacket bridge pier subjected to quasi-static tests. The Finite Element Method (FEM) results demonstrated a significant correlation with the experimental response, particularly in terms of the load-displacement curve failure mode. Once the model was validated, various alternative designs were numerically tested to evaluate the impact of each model on the load-bearing capacity. These designs included altering the height of the CFRP sheet, adjusting the height and congestion of the CFRP bar, and comparing the performance of the concrete jacket with and without the CFRP sheet. After reinforcing the CFRP sheets and incorporating Near-Surface-Mounted (NSM)-CFRP bars, the reinforcement system, along with the new concrete jacket, effectively transferred the integrity of the broken pier area and maintained a constant load-bearing capacity for the bridge pier. However, when the CFRP sheet was added to the aforementioned system, the load capacity of the bridge pier increased by more than 60%. Therefore, it can be concluded that seismic enhancement techniques utilizing CFRP sheets and mounted NSM-CFRP bars are successful in enhancing the strength and resilience of the concrete bridge pier.